Evaluation of two laboratory methods for the diagnosis of hydatidosis - Batista, Generosa (2009)
Hydatidosis, also known as hydatid cyst, is caused by the larval stages of the parasite Echinococcus granulosus. Its diagnostic relies mainly on clinical findings, epidemiology, and imaging techniques supported by serological tests. Surgery is the commonest treatment; it is important to have a definitive diagnosis of hydatidosis before surgery, to avoid the spread of the cysts during the procedure. In this study, two immunoserologic tests for the diagnostic of hydatidosis are compared: Enzyme-linked Immunosorbent Assay (ELISA) for immunoglobulin G; and Fluoro-Enzyme Immunoassay (FEIA) for immunoglobulin E. Of the 55 patients included in this study are in a pre-surgery stage, 31% have a calcified hydatic cyst, 54,5% a not calcified cyst and 14.5% have no hydatic cyst. Both tests had the same specificity (87.5%), and the sensitivity of the ELISA IgG was lower (63.8%) than the FEIA IgE (76.6%). The correlation observed between both tests was good (r = 0.726, p < 0.05).